PRODUCTIVITY DETERMINANTS AND THEIR EFFECT IN THE PLANTING YIELD FOR THE CROPS OF MAIN VEGETABLES IN TELKEEF DISTRICT - Hanaa Daowd; Safaa J. Abd (Mesopotamia Journal of Agriculture)
This research aims at studying the determinants that affect of the productivity and which in turn is reflected in the return. Data were obtained through a questionnaire of a sample amounted to (105) farms for summer season 2010 from farmers of Naieem society. Research hypothesis that included determinants affect productivity of vegetable crops, which in turn may affect revenue (profit farm). Survey variables included (age, experience, number of family farms, land, land type, kind of crop, labor income, costs of agriculture, Tillage, fertilization, type agriculture, harvesting, funding type, input prices, marketing, sale prices, climatic factors, crop price fluctuations, support State). Through the use of factor analysis showed that every, marketing, cost, experience, income and crop price fluctuations a significant impact on the productivity variable and therefore will have an effect on the farm where the profit of all these factors may make farms of non productivity.